How and when screens are used: comparing different screen activities and sleep in Norwegian university students - Hjetland, Gunnhild Johnsen; Skogen, Jens Christoffer; Hysing, Mari; Gradisar, Michael; Sivertsen, Børge (Frontiers in Psychiatry, 2025)
IntroductionScreen use in bed has become a widespread habit, particularly among young people. This behavior has been associated with poor sleep, with some studies indicating that social media use may be especially detrimental. However, there is a scarcity of research directly comparing the relationship between various screen activities and sleep, and most existing studies focus on adolescents rather than young adults. This study aims to explore the relationship between screen use in bed and sleep among students, specifically comparing social media use to other screen-based activities.MethodsThis study utilized data from the cross-sectional Students’ Health and Wellbeing Study of 2022 and included n=45,202 participants aged 18-28 years. Regression analyses were used to assess the relationship between screen time in bed and sleep, comparing social media use with other activities.ResultsA one-hour increase of screen time after going to bed was associated with 59% higher odds of having symptoms of insomnia and a reduction in sleep duration of 24 minutes. The associations between screen time and sleep outcomes did not differ for social media use versus other activities. Independent of screen time, participants who exclusively used social media had lower odds of insomnia and longer sleep duration compared to those engaging in other activities or a mix of activities.DiscussionThe present study found that increased screen time in bed is linked to poorer sleep, across activity type. Future research should refine classifications, assess specific content, and employ experimental approaches to determine causal mechanisms.